Simulation of reactive mixing behaviors inside micro-droplets by a lattice Boltzmann method. (18th May 2018) - Fu, Yuhang; Bai, Lin; Zhao, Shufang; Zhang, Xiong; Jin, Yong; Cheng, Yi
Highlights: Presented a LBM approach to model mixing process with chemical reactions in multiphase flow. Demonstrated liquid mixing with parallel competing reaction inside moving micro-droplet. Applied standard deviation σ and segregation index Xs for describing mixing and reactions. Abstract: The Villermaux/Dushman competing parallel reactions are modeled into a multiphase/multicomponent lattice Boltzmann method (LBM) to theoretically investigate the interplay between mixing and reactions in droplet-based microfluidics. To quantify the mixing and reaction efficiency inside the droplets, the standard deviation σ representing the pure mixing performance without reaction and the segregation index Xs reflecting mixing index with simultaneous chemical reactions are calculated based on the simulation results. The results show that the species transport can be evidently intensified by matching the flow recirculation and the appropriate initial distribution of reactants. We further demonstrate that the reaction selectivity could be improved by tuning droplet flow conditions or adding internal baffles to arbitrarily adjust the position of recirculation inside droplet.